Enterocytozoon bieneusi infection disrupts bile acid metabolism in the wild rodent gut microbiota: adaptive shifts in microbial metabolism and community structure - Shang, Kai-Meng; Ma, He; Wei, Yong-Jie; Zhao, Ji-Xin; Qin, Ya; Li, Jian-Ming; Zhao, Zi-Yu; Yu, Hai-Long; Zhao, Quan; Chen, Bei-Ni; Elsheikha, Hany M.; Zhang, Xiao-Xuan; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionBile acids (BAs) are central to host–microbiota interactions, yet their metabolism in wild rodents remains poorly characterized. This study aimed to explore the genomic potential of gut microorganisms in wild rodents for BA metabolism and its implications for host adaptation and pathogen interactions.MethodsWe reconstructed 6,332 genomes from the gut microbiota of wild rodents and performed genome-resolved metabolic profiling. Comparative analyses were conducted across host species, including humans, pigs, laboratory mice, and chickens. Functional enrichment was further assessed in relation to glycoside hydrolase families and Enterocytozoon bieneusi infection status.ResultsA total of 5,208 genomes were identified as participants in key BA metabolic pathways, including deconjugation, oxidation, and dihydroxylation, predominantly from Bacillota_A and Bacteroidota. Notably, Muribaculaceae and CAG-485 lineages within Bacteroidota encoded bile salt hydrolase (BSH). Cross-species comparisons revealed a striking absence of 7β-hydroxysteroid dehydrogenase (7β-HSDH) in laboratory mice, indicating their limited suitability for modeling intestinal BA metabolism. BSH-encoding genomes were significantly enriched in glycoside hydrolase families GH13 and GH16, suggesting a potential link between BA transformation and carbohydrate metabolism. Furthermore, Enterocytozoon bieneusi infection was associated with a marked increase in BA-related microbial taxa in wild rodents.DiscussionOur findings highlight the intricate interconnections between gut microbial functions, BA metabolism, and pathogen interactions. The absence of 7β-HSDH in laboratory mice underscores wild rodents as potentially more suitable models for BA research. These results open new avenues for understanding microbiome-driven host adaptation and health.